2022
DOI: 10.1038/s41598-022-07723-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of cervical cancer identification by photonic method combined with machine learning

Abstract: Cervical cancer is one of the most commonly appearing cancers, which early diagnosis is of greatest importance. Unfortunately, many diagnoses are based on subjective opinions of doctors—to date, there is no general measurement method with a calibrated standard. The problem can be solved with the measurement system being a fusion of an optoelectronic sensor and machine learning algorithm to provide reliable assistance for doctors in the early diagnosis stage of cervical cancer. We demonstrate the preliminary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 56 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…In Kruczkowski et al’s study, the time needed to train for the Naïve Bayes and CNN algorithms varied from 7.54 ms to 5320 ms. The prediction time for cervical cancer by the Naïve Bayes and RF algorithms varied from 1.81 ms to 15.5 ms, and the accuracies differed [ 76 ]. Elakkiya et al reported an average of 0.2 s to classify the cervical lesion using a hybrid deep learning technique that combined small-object detection generative adversarial networks (SOD-GAN) and the fine-tuned stacked autoencoder (F-SAE).…”
Section: Resultsmentioning
confidence: 99%
“…In Kruczkowski et al’s study, the time needed to train for the Naïve Bayes and CNN algorithms varied from 7.54 ms to 5320 ms. The prediction time for cervical cancer by the Naïve Bayes and RF algorithms varied from 1.81 ms to 15.5 ms, and the accuracies differed [ 76 ]. Elakkiya et al reported an average of 0.2 s to classify the cervical lesion using a hybrid deep learning technique that combined small-object detection generative adversarial networks (SOD-GAN) and the fine-tuned stacked autoencoder (F-SAE).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, researchers have advocated the use of MLP in cervical cancer prediction due to its respectable classification accuracy [ 10 , 18 , 19 , 20 , 25 , 26 , 29 , 30 ]; therefore, MLP is selected for optimization by GA in this study. In addition, various researchers used SVM, RF, LR DT, KNN, NB, LDA, and AdaBoost to classify cervical cancer [ 4 , 9 , 10 , 11 , 13 , 22 , 23 , 30 , 31 , 32 , 33 ]. Those algorithms are among the most common classification algorithms in modeling medical datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Feature selection is the process of minimizing the number of input variables when creating a predictive model. The number of input variables might be reduced to decrease the computational cost of modeling and, in some circumstances, to improve the model’s performance [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, various Feature Selection Technique (FST) methods were applied to the transformed datasets to predict cervical cancer or identify important risk factors [ 75 , 76 ]. The machine learning algorithm is fused with an optoelectronic sensor to realise rapid sample measurement and the automatic classification of results [ 77 ]. Several meta-analyses confirmed the diagnostic performance of machine learning or deep learning algorithms in cervical cancer recognition [ 78 , 79 ].…”
Section: Detection Of Premalignancy and Malignancy Of The Uterine Cervixmentioning
confidence: 99%